Evaluate sin²
- sin²
Answers
Answered by
26
we have to find value of sin²82 1/2° - sin²22 1/2°
use algebraic formula, a² - b² = (a - b)(a + b)
so, sin²82 1/2° - sin²22 1/2° = [sin82 1/2° + sin22 1/2° ][sin82 1/2° - sin22 1/2° ]
use formula, sinC + sinD = 2sin(C + D)/2.cos(C - D)/2
sinC - sinD = 2cos(C + D)/2. sin(C - D)/2
so, sin82 1/2° + sin22 1/2° = 2sin52 1/2° . cos30°
= 2 sin52 1/2° (√3/2) = √3sin52 1/2°
similarly, sin82 1/2° - sin22 1/2° = 2cos52 1/2°sin30°
= 2cos52 1/2° (1/2) = cos52 1/2°
now, [sin82 1/2° + sin22 1/2° ][sin82 1/2° - sin22 1/2° ] = √3sin52 1/2° cos52 1/2°
= √3/2(2sin52 1/2° cos52 1/2°)
we know, 2sinx. cosx = sin2x
so, 2sin52 1/2° cos52 1/2° = sin105°
= √3/2 sin105°
= √3/2 sin(60° + 45°)
= √3/2 [ sin60°.cos45° + cos60° sin45°]
= √3/2 × (√3 + 1)/2√2
= (3 + √3)/4√2
use algebraic formula, a² - b² = (a - b)(a + b)
so, sin²82 1/2° - sin²22 1/2° = [sin82 1/2° + sin22 1/2° ][sin82 1/2° - sin22 1/2° ]
use formula, sinC + sinD = 2sin(C + D)/2.cos(C - D)/2
sinC - sinD = 2cos(C + D)/2. sin(C - D)/2
so, sin82 1/2° + sin22 1/2° = 2sin52 1/2° . cos30°
= 2 sin52 1/2° (√3/2) = √3sin52 1/2°
similarly, sin82 1/2° - sin22 1/2° = 2cos52 1/2°sin30°
= 2cos52 1/2° (1/2) = cos52 1/2°
now, [sin82 1/2° + sin22 1/2° ][sin82 1/2° - sin22 1/2° ] = √3sin52 1/2° cos52 1/2°
= √3/2(2sin52 1/2° cos52 1/2°)
we know, 2sinx. cosx = sin2x
so, 2sin52 1/2° cos52 1/2° = sin105°
= √3/2 sin105°
= √3/2 sin(60° + 45°)
= √3/2 [ sin60°.cos45° + cos60° sin45°]
= √3/2 × (√3 + 1)/2√2
= (3 + √3)/4√2
rahulsingh4417:
Sir will u plz help me plz
Answered by
29
Answer:
Step-by-step explanation:
Formula used:
First we calculate
sin105
=sin(60+45)
=sin60 cos45+cos60 sin45
Similar questions